Subjektifitas Bacaaan Sastra dan Implikasinya terhadap Pembelajaran Sastra - Adi Probo Laksono; Djoko Saryono; Anang Santoso (Jurnal Pendidikan: Teori, Penelitian, dan Pengembangan, 2021)
Abstract: The construction of agent subjectivity in learning, from a social point of view, is formed through learning. The subjectivity of literature lecturer readings is formed through structuration carried out by educational institutions. Therefore, this study aims to (1) describe the disposition of literary readings of literature lecturers and (2) describe the objectivity of the subjectivity of literature lecturers to literary readings. This research is a qualitative research with descriptive method. The data analysis in this research is based on Pierre Bourdieu's theory of cultural reproduction. The results of this study indicate that the socio-cultural background is the basis for the initial formation of value subjectivity in literary reading. The accumulated experience during the education period structures the subjectivity of literature lecturers in choosing literary readings. The objectification of the subjectivity of literature lecturers is manifested in the form of choosing reading materials that are suggested to students in college learning.Abstrak: Konstruksi subjektivitas agen dalam pembelajaran, dalam sudut pandang social, terbentuk melalui pembelajaran. Subjektivitas bacaan dosen sastra dibentuk melalui strukturasi yang dilakukan oleh lembaga pendidikan. Oleh sebab itu, penelitian ini bertujuan untuk (1) mendeskripsikan disposisi bacaan sastra dosen sastra dan (2) mendeskripsikan objektivikasi subjektivitas dosen sastra terhadap bacaan sastra Penelitian ini merupakan penilitian kualittatif dengan metode deskriptif. Analisis data pada peneilitian ini didasarkan pada pemikiran teori reproduksi budaya Pierre Bourdieu. Hasil penelitian ini menunjukkan bahwa latar belakang sosio-budaya menjadi dasar pembentukan awal subjektivitas nilai pada bacaan sastra. Akumulasi pengalaman pada masa pendidikan menstrukturkan subjektifitas dosen sastra dalam memilih bacaan sastra. Objektivikasi subjektifitas dosen sastra diwujudkan dalam bentuk pemilihan bahan bacaan yang disarankan kepada mahasiswa pada pmebelajaran di perguruan tinggi.